Catalogue of the free-living and arthropod-associated Laelapidae Canestrini (Acari: Mesostigmata), with revised generic concepts and a key to genera - de Moraes, Gilberto José; Moreira, Grazielle Furtado [UNESP]; Freire, Renata Angélica Prado [UNESP]; Beaulieu, Frédéric; Klompen, Hans; Halliday, Bruce (Magnolia Press, 2022)
The cosmopolitan mite family Laelapidae includes both free-living predatory species and species associated with arthropods, mammals or birds. This work presents a list of free-living and arthropod-associated species of laelapids, with corresponding taxonomic information and references. It includes 1088 species (in addition to three subspecies) assigned to 73 genera, 61 new combinations and two new synonymies at the generic level. Laelaps (Apolaelaps) Silvestri is raised to the generic level. Many of the species described before about 1950 are poorly characterised and cannot be classified with confidence at the family or generic level. Hence, ten genera, one subgenus, 121 species (ca. 70% of which were reported as Hypoaspis Canestrini or Laelaps (Hypoaspis) Canestrini) and one subspecies, are considered incertae sedis, because of their inadequate morphological characterisation in the literature. Some of these may not even belong to the Laelapidae or to the groups of interest for this publication. A total of 89 species, 30 genera, one subgenus, one tribe and one subfamily previously associated with genera treated in this catalogue are now placed in other families or, less commonly, in laelapid genera not considered here because they are considered essentially vertebrate parasites (taxa excluded). Twenty-six other species (one cited as a “variety”) are cited as nomina nuda. An illustrated key to the 73 genera included in the catalogue along with revised generic diagnoses are provided.
Keywords: arthropod-associated mites; free-living mites; predatory mites; taxonomy